Community perceptions of the problems associated with companion animals in Esperanza city, Santa Fe, Argentina (FAVE Sección Ciencias Veterinarias, 2024)
Overpopulation and free-roaming animals in public spaces generate diverse impacts on animal welfare, biodiversity, and public health with the occurrence of zoonotic diseases, animal bites, and traffic accidents.Programs to manage the problem must be designed, implemented, and adapted to each local reality. In that sense, the community's perception of the problem is a fundamental input that improves the chances of success of said programs.To know the community's perceptions about free animals on public roads in the city of Esperanza (Santa Fe), an observational, transversal, and descriptive study was carried out in 2019. The inhabitants were questioned (N= 115) through a semi-structured survey.The community considers free animals on streets as a relevant problem, including insecurity or environmental issues (62%). At the same time, zoonoses are not mentioned (2%) as having main impacts on public health. Individual actions along with those executed by the State are perceived as part of the solution (45.6%). However, it was observed that the perception of the existence of the problem is not associated with individual actions and attitudes aimed at avoiding it.
Keywords: public health; companion animals; animal populations; perceptions